A snapshot on crowdfunding - Joachim Hemer (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2011)
This article addresses crowdfunding, a relatively new form of informal financing of pro-jects and ventures. It describes its principle characteristics and the range of players in this market. The different business models of crowdfunding intermediaries are explored and illustrated. A first attempt is made to classify the different forms of funding and business models of crowdfunding intermediaries. Based on the available empirical data the paper discusses the economic relevance of crowdfunding and its applicability to start-up financing and funding creative ventures and research projects.
urn:nbn:de:0011-n-1859318
Keywords: 330; Regionale Konzentration